2012
DOI: 10.1002/art.33411
|View full text |Cite
|
Sign up to set email alerts
|

Selective up‐regulation of the soluble pattern‐recognition receptor pentraxin 3 and of vascular endothelial growth factor in giant cell arteritis: Relevance for recent optic nerve ischemia

Abstract: Objective. To assess local expression and plasma levels of pentraxin 3 (PTX3) in patients with giant cell arteritis (GCA).Methods. Plasma and serum samples were obtained from 75 patients with GCA (20 of whom had experienced optic nerve ischemia in the previous 3 weeks and 24 of whom had experienced symptom onset in the previous 6 months and had no history of optic nerve ischemia) and 63 controls (35 age-matched healthy subjects, 15 patients with rheumatoid arthritis, and 13 patients with chronic stable angina)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 51 publications
8
53
1
Order By: Relevance
“…This was surprising given that Baldini et al reported a sixfold upregulation of pentraxin-3 in GCA compared with healthy controls or controls with rheumatoid arthritis. 8 Concentration of pentraxin-3 in controls for this study (3.35 ng/mL) was similar to Baldini et al (3.97 ng/mL) but concentration in GCA patients (5.48 ng/mL) was significantly lower than in Baldini et al (23.3 ng/mL). This suggests that the groups of GCA patients in the two studies are different.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This was surprising given that Baldini et al reported a sixfold upregulation of pentraxin-3 in GCA compared with healthy controls or controls with rheumatoid arthritis. 8 Concentration of pentraxin-3 in controls for this study (3.35 ng/mL) was similar to Baldini et al (3.97 ng/mL) but concentration in GCA patients (5.48 ng/mL) was significantly lower than in Baldini et al (23.3 ng/mL). This suggests that the groups of GCA patients in the two studies are different.…”
Section: Discussionsupporting
confidence: 84%
“…15 The main source of VEGF is CD68 macrophages and giant cells within the vessel wall, 15 16 and this local production of VEGF is mirrored by raised serum levels of VEGF in patients with GCA compared with controls. 8 Furthermore, allelic variants in VEGF confer different susceptibility to development of GCA 17 18 and certain polymorphisms are associated with increased risk of ischaemic complications. 18 19 VEGF may function in GCA either to compensate for ischaemia in the thickened artery, 20 or to drive inflammation by increasing new blood vessels which are the primary expressers of adhesion molecules involved in recruitment of inflammatory cells.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients diagnosed with GCA by 2050 is projected to be over 3 million in Europe, North America, and Oceania, representing a significant clinical and financial challenge [8]. Several previous reports have described potential serological markers for GCA [9][10][11][12][13][14][15][16][17][18], among them cytokines, chemokines, growth factors, cell adhesion molecules, and matrix metalloproteinases (MMPs). In 2000, Weyand et al emphasized that interleukin (IL)-6 may act as a biological marker of GCA activity in untreated and treated GCA patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, serum IL-6 and IL-1β levels have been found strongly increased in patients with active GCA (74, 99) and associated with disease activity (100, 101). While the precise cellular source of the excess IL-6 and IL-1β has not been determined, highly activated macrophages and DC in the vasculitic lesions emerge as the likely producers (102).…”
Section: Giant-cell Arteritismentioning
confidence: 97%